Sturge–Weber syndrome in a 6-year-old girl - D. E. C. PEREZ, J. S. PEREIRA NETO, E. GRANER, & M. A. LOPES (Paediatric Dentistry, 2005)
Sturge–Weber syndrome (SWS), or encephalotrigeminal angiomatosis, is a rare, non-hereditary condition characterized by a facial cutaneous vascular nevus (nevus flammeus or port wine stain) in association with leptomeningeal angiomatosis [1,2].